Multivariate framework for introspecting the motivational factors for satisfaction in HR profession - Chaki, Mainak Ranjan; Guha, Banhi; Biswas, Sanjib; Bandyopadhyay, Gautam; Bhattacharjee, Malay (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Human Resource Management (HRM) has evolved as a strategic function for an organization, contributing significantly towards organizational development, business growth and societal development. The current work fills the gap in the literature by unveiling the higher order motivational needs driving the satisfaction of human resource (HR) professionals in their job roles. Further, it intends to delve into the causal relationship of the underlying factors. Methods: A three stage detailed exploratory and mediation analysis is carried out. In the first stage, a focused group interview of 25 senior HR professionals was conducted. These professionals are all holding the role of Chief Human Resource Officers(CHROs) in their respective organizations. In the second stage, a large scale exploratory analysis is carried out based on the responses of 423 respondents. Stage three confirms the interrelationship among the underlying factors obtained through the EFA. Results: The results of the primary survey of 423 professionals reveal the three underlying factors such as identity, power and societal leadership (SL) that motivate HR professionals and drive their satisfaction in the job role. Further, it is observed that power mediates the interrelationship between identity and SL. Conclusion: The results of the survey strongly suggest that there exists a high degree of correlation between identity, power, and societal relationships when it comes to HR professionals.